Exploring the Link between Whitening Cream Practices and Skin Cancer Awareness among Bangladeshi Female Youths (IUBAT Review, 2026)
The increasing use of skin-whitening creams among young women in Bangladesh poses serious public health concerns due to the potential risks associated with harmful ingredients such as mercury and hydroquinone. This study investigates the knowledge, perceptions, and practices related to skin-whitening product use and their association with skin cancer awareness among female students aged 15–30 years in Dhaka. A cross-sectional study was conducted involving 500 participants selected through stratified random sampling from five educational institutions in the Uttara Sector-10 area. Data were collected through structured face-to-face interviews using a comprehensive questionnaire. Results revealed that only 28% of participants had adequate knowledge of skin cancer, while the majority used whitening products influenced by peer pressure, social media, and beauty norms. Correlation analysis indicated a negative relationship between knowledge level and whitening cream usage (r = -0.42, p < 0.05) and a strong positive correlation between social media influence and product use (r = 0.62, p < 0.01). Common side effects included skin irritation and rashes. The findings underscore the urgent need for targeted public health campaigns, inclusion of skincare education in curricula, and stricter regulatory measures to promote safer cosmetic practices and informed decision-making among young women.IUBAT Review—A Multidisciplinary Academic Journal, 8(2): 22-44